Effect of Pipe Bends on the Low-Frequency Torsional Guided Wave Propagation - WU, Wenjun; WANG, Junhua (Archives of Acoustics, 2020)
Wave motion in pipe bends is much more complicated than that in straight pipes, thereby changing considerably the propagation characteristics of guided waves in pipes with bends. Therefore, a better understanding of how guided waves propagate in pipe bends is essential for inspecting pipelines with bends. The interaction between a pipe bend and the most used non-dispersive torsional mode at low frequency in a small-bore pipe is studied in this paper. Experiments are conducted on a magnetostrictive system, and it is observed that T(0,1) bend reflections and mode conversions from T(0,1) to F(1,1) and F(2,1) occur in the pipe bend. The magnitude of the T(0,1) bend reflections increases with increasing propagation distance and excitation frequency. The amplitude of the mode-converted signals also increases with increasing propagation distance, but it decreases with increasing excitation frequency. Because of their longer bent path, the test signals for a pipe bend with a bending angle of 180X are much more complicated than those for one with a bending angle of 90X. Therefore, it is even more difficult to scan a bent pipe with a large bending angle. The present findings provide some insights into how guided waves behave in pipe bends, and they generalize the application of guided-wave inspection in pipelines.